Reservoir engineering handbook - Ahmed, Tarek H., 1946- (Elsevier Ltd. : Gulf Professional Publishing, 2019)
Reservoir Engineering Handbook, Fifth Edition, equips engineers and students with the knowledge they require to continue maximizing reservoir assets, especially as more reservoirs become complex, more multilayered, and unconventional in their extraction method. Building on the solid reputation of the previous edition, this new volume presents critical concepts, such as fluid flow, rock properties, water and gas coning, and relative permeability in a straightforward manner. Water influx calculations, lab tests of reservoir fluids, oil and gas performance calculations, and other essential tools of the trade are also introduced, reflecting on today's operations. New for this edition is an entire new chapter devoted to enhanced oil recovery techniques, including WAG. Critical new advances in areas such as well performance, waterflooding and an analysis of decline and type curves are also addressed, along with more information on the growing extraction from unconventional reservoirs. Practical and critical for new practicing reservoir engineers and petroleum engineering students, this book remains the authoritative handbook on modern reservoir engineering and its theory and practice.